A Review of Gynecologic Oncology in the Global Setting: Educating and Training the Next Generation of Women's Health Providers. Issue 1 (January 2019) - Sullivan, Stephanie A.; Stringer, Elizabeth; Van Le, Linda
Abstract : Importance: Women in low- and middle-income countries (LMICs) are responsible for the stability of their families. Child survival is directly linked to the health and well-being of their mother. Cancer is the leading cause of morbidity and mortality worldwide, and the incidence and mortality for women from cancer are projected to increase over the coming decades. Gynecologic cancer outcomes are improved when women are cared for by a gynecologic oncologist; however, there are limited specialized providers in LMICs. Increasing interest and involvement from specialists in the United States will improve partnerships abroad and the care of women worldwide. Objective: To summarize the importance of global gynecologic oncology care and the current data for US trainees in obstetrics and gynecology to participate in clinical and capacity-building opportunities. Evidence Acquisition: We performed a PubMed literature search for articles pertaining to the topic of global health education in obstetrics and gynecology and gynecologic oncology specifically. Results: Many obstetric and gynecologic residency programs offer international opportunities, but these are less than those in other specialties and are more frequently focused in obstetrics. Many gynecologic oncology fellowship programs offer international experiences for fellows; however, the time and resources required are limited. Several US and international programs are ongoing to improve capacity building for gynecologic oncology in LMICs with local trainees. Conclusions and Relevance: Training and care in gynecologic oncology care worldwide are improving through efforts at multiple levels. Continued efforts are needed to improve US trainee international education and experience. Target Audience: Obstetricians and gynecologists, family physicians Learning Objectives: After completing this activity, the learner should be better able to examine the unique role of women in LMICs; identify the limitations in gynecologic oncology care in LMICs; value the importance of global health exposure during medical training for U.S. physicians; and analyze initiatives that can improve training in gynecologic oncology for global providers.